ANALISIS STRUKTURAL DAN NILAI MORAL DALAM CERPEN "GUGATAN" KARYA SUPARTIKA - Arianti, Ira (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
To study the benefits of literary works must analyze frist, in analyzing must have a special knife assessment, one of them structrular studies. A short story made by the writer for the analysis material ini this study because it discusses its unique structure and gives the impression of assessing moral values. This analysis aims to (1) describe the relationship between the intrinsic elements of the short story “Lawsuit” by Supartika (2) describe the moral values in the story. This research uses descriptive qualitative methods. With the step of collecting date (1) Reading the short story “Lawsuit” intensively (2) Analyzing the intrinsic unscored short story and describing it (3) Recording data in the form of text. Dialougue in accordance with the short story (4) The library method used in searching the literature (5) Analyzing moral values in the short story  “Lawasuit” and describe it. Form the results the analysis conducted in the shurt story “Lawsuit”by Supartika and describe it. From the result of the analysis conducted in the shurt story “Lawsuit” by Supartika has a link between elements and moral values that can be obtained by the reader.